2021
DOI: 10.3390/nano11071833
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Arrangements of Graphene-like ZnO

Abstract: ZnO, which can exist in various dimensions such as bulk, thin films, nanorods, and quantum dots, has interesting physical properties depending on its dimensional structures. When a typical bulk wurtzite ZnO structure is thinned to an atomic level, it is converted into a hexagonal ZnO layer such as layered graphene. In this study, we report the atomic arrangement and structural merging behavior of graphene-like ZnO nanosheets transferred onto a monolayer graphene using aberration-corrected TEM. In the region to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Several nonlayered materials can be synthesized as 2D materials using the above-mentioned method. Among them, ZnO, which is a transition metal oxide, can be converted to various nanostructures. Recent theoretical and experimental studies have shown that when ZnO is as thin as an atomic layer, its wurtzite structure can transform into a stable 2D monolayer structure similar to that of graphene, accordingly named graphene-like ZnO (or g-ZnO). The structure of g-ZnO is chemically stable according to both theoretical calculations and experimentation. When synthesized as large-area nanosheets, the application range of g-ZnO is broadened owing to the expansion of its surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Several nonlayered materials can be synthesized as 2D materials using the above-mentioned method. Among them, ZnO, which is a transition metal oxide, can be converted to various nanostructures. Recent theoretical and experimental studies have shown that when ZnO is as thin as an atomic layer, its wurtzite structure can transform into a stable 2D monolayer structure similar to that of graphene, accordingly named graphene-like ZnO (or g-ZnO). The structure of g-ZnO is chemically stable according to both theoretical calculations and experimentation. When synthesized as large-area nanosheets, the application range of g-ZnO is broadened owing to the expansion of its surface area.…”
Section: Introductionmentioning
confidence: 99%
“…However, although zinc dialkoxides exhibit easier handling in air moisture conditions compared to dialkyl zinc or alkyl zinc alkoxides, only a few reports on the hydrolysis and condensation of zinc dialkoxides are reported in the literature. , We have recently reported, both theoretically and experimentally, that the formation of small hydroxyl-terminated (ZnO) n planar clusters with n < 6 is possible via the hydrolysis–condensation of zinc dimethoxide. , However, regardless of the preparation methodology, characterizing these g-ZnO structures has so far been a hard task. It is well-known that the g-ZnO structures are reported to be stable only in their monolayered and bilayered structures while higher-order layered structures (more than 3 layers) are thermodynamically stable on Wurtzite structures based on high-resolution transmission electron or scanning tunneling microscopies. , Nonetheless, the first experimental Raman spectra for bilayer g-ZnO structures have been reported just recently in a joint computational and experimental study using the tip-enhanced Raman spectroscopy (TERS) instrumentation technique. , Although this extremely powerful technique provided the first experimental Raman spectra features of this material, on the other hand, it was only related to fairly small regions at the edge of the samples. Thus, not only more preparation techniques but also further studies using other instrumentation techniques are needed to provide more representative information about the formation of g-ZnO structures.…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue “2D Nanostructures for Optoelectronic and Green Energy Devices”, we have collected nine high-quality, original research papers and one comprehensive review paper by outstanding scientists and engineers from relevant fields, covering the topics in optical properties and couplings in 2D nanostructures, [ 5 , 6 , 7 , 8 ] spectroscopic analysis in atomic scale, [ 9 ] 2D transistors, [ 10 , 11 ] 2D optoelectronics, [ 12 ] and 2D energy storage applications [ 13 , 14 ].…”
mentioning
confidence: 99%
“…Singh et al [ 7 ] and Pandey et al [ 8 ] reported optical coupling in nanostructures and substrates, which can be used in nanophotonics and detection applications. Yoon et al [ 9 ] reported the atomic arrangement of graphene-like ZnO examined using transmission electron spectroscopy. A-Rang Jang [ 11 ] reported graphene contact in a 2D transistor, which was effective in lowering the Schottky barrier in metal-2D semiconductor contact.…”
mentioning
confidence: 99%